Beacon v2 and Beacon networks: A "lingua franca" for federated data discovery in biomedical genomics, and beyond. Issue 6 (8th April 2022) - Rambla, Jordi; Baudis, Michael; Ariosa, Roberto; Beck, Tim; Fromont, Lauren A.; Navarro, Arcadi; Paloots, Rahel; Rueda, Manuel; Saunders, Gary; Singh, Babita; Spalding, John D.; Törnroos, Juha; et al.
Abstract: Beacon is a basic data discovery protocol issued by the Global Alliance for Genomics and Health (GA4GH). The main goal addressed by version 1 of the Beacon protocol was to test the feasibility of broadly sharing human genomic data, through providing simple "yes" or "no" responses to queries about the presence of a given variant in datasets hosted by Beacon providers. The popularity of this concept has fostered the design of a version 2, that better serves real‐world requirements and addresses the needs of clinical genomics research and healthcare, as assessed by several contributing projects and organizations. Particularly, rare disease genetics and cancer research will benefit from new case level and genomic variant level requests and the enabling of richer phenotype and clinical queries as well as support for fuzzy searches. Beacon is designed as a "lingua franca" to bridge data collections hosted in software solutions with different and rich interfaces. Beacon version 2 works alongside popular standards like Phenopackets, OMOP, or FHIR, allowing implementing consortia to return matches in beacon responses and provide a handover to their preferred data exchange format. The protocol is being explored by other research domains and is being tested in several international projects. Abstract : Beacon is a basic data discovery protocol issued by the Global Alliance for Genomics and Health (GA4GH). Beacon version 2 serves real world requirements and addresses the needs of clinical genomics research and healthcare, allowing implementing consortia to return matches in beacon responses and provide a handover to their preferred data exchange format. Beacon is designed as a "lingua franca" to bridge data collections hosted in software solutions with different and rich interfaces. Beacon queries could be send to Beacon instances directly or via Beacon networks. The response could be yes/no, counts or details if the user is properly authorized.